Investigation of Genetic Relatedness of Brucella Strains in Countries Along the Silk Road - Liu, Zhiguo; Wang, Chengling; Wei, Kongjiao; Zhao, Zhongzhi; Wang, Miao; Li, Dan; Wang, Heng; Wei, Qiang; Li, Zhenjun (Frontiers in Veterinary Science, 2021)
In this study, MLVA (multiple-locus variable-number tandem repeat analysis) genotype data of Brucella strains from 11 countries along the Silk Road were downloaded from the MLVAbank. MLVA data of strains were applied to the constructed Minimum Spanning Tree to explore the species/biovars distribution, geographic origins, and genetic relationships of the strains analyzed. Moreover, whole-genome sequencing–single-nucleotide polymorphism (WGS-SNP) phylogenetic analysis of the genome of Brucella melitensis strains from GenBank was performed to discriminate the relatedness of strains further and investigate the transmission pattern of B. melitensis brucellosis. A total of 1,503 Brucella strains were analyzed in this study: 431 Brucella abortus strains (29.8%), 1,009 B. melitensis strains (65.7%), and 63 Brucella suis strains (4.5%). B. melitensis biovar 3 was the dominant species and was shown to be widespread in all of the examined regions, suggesting that the prevention and surveillance of the B. melitensis population are a main challenge in these countries. A wide host spectrum was observed for this Brucella population; many animal reservoirs are a potential reason for the continuous brucellosis circulation in these countries. Although the B. abortus strains from the examined regions had common geographic origins, only a few shared genotypes were observed in different countries. These data revealed that the majority of B. abortus strains were spreading within the national borders. However, the B. melitensis strains from Italy originated from a Western Mediterranean lineage; strains from the other 10 countries originated from Eastern Mediterranean lineage, and this lineage was shared by strains from three to nine different countries, suggesting that the introduction and reintroduction of the disease in the 10 countries might have occurred in the past. Furthermore, the most shared MLVA-16 genotypes were formed in the B. melitensis strains from China, Kazakhstan, and Turkey, suggesting that the introduction and trade in sheep and goats have occurred frequently in these countries. WGS-SNP analysis showed that the B. melitensis in this study originated from the Malta (Italy) region. According to their territorial affiliation between four clade strains from these countries in genotype B, the absence of a clear differentiation suggests that strains continuously expand and spread in countries along with Silk Road. Active exchange and trade of animals (sheep and goats) among these countries are reasonable explanations. B. suis strains from different nations showed unique geographic origins and epidemiological characteristics. Therefore, there is an urgent need for the control of transfer and trade of infected sheep (goats) in countries along the Silk Road, namely, the strengthening of the entry–exit quarantine of sheep and goats and improvements in the diagnosis of animal brucellosis.